2011
DOI: 10.4028/www.scientific.net/kem.485.195
|View full text |Cite
|
Sign up to set email alerts
|

Growth of (111)-Oriented Epitaxial Bi(Mg<sub>0.5</sub>Ti<sub>0.5</sub>)O<sub>3</sub> Films and their Characterization

Abstract: Crystal structure and electrical properties were investigated for Bi (Mg0.5Ti0.5)O3 films grown on (111)c- and (100)c-oriented SrRuO3//SrTiO3 substrates by pulsed laser deposition. Epitaxial films consisting of a single phase of perovskite were obtained on the (111) substrates. Additionally, the ferroelectricity was ascertained not only from the polarization - electric field hysteresis loops, but also from the piezoelectric response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…6) Therefore, we have paid attention to Bi-based perovskite oxides as Pb-and alkali-metal-free piezoelectric materials for MEMS applications. [7][8][9][10][11][12][13][14] It is widely known that piezoelectric materials with the composition near the phase boundary between tetragonal and nontetragonal symmetries, especially rhombohedral symmetry, show the largest piezoresponse. [15][16][17] Investigation of the phase boundary in a Bi-based perovskite oxide system is a key to achieving a superior piezoelectric property.…”
Section: Introductionmentioning
confidence: 99%
“…6) Therefore, we have paid attention to Bi-based perovskite oxides as Pb-and alkali-metal-free piezoelectric materials for MEMS applications. [7][8][9][10][11][12][13][14] It is widely known that piezoelectric materials with the composition near the phase boundary between tetragonal and nontetragonal symmetries, especially rhombohedral symmetry, show the largest piezoresponse. [15][16][17] Investigation of the phase boundary in a Bi-based perovskite oxide system is a key to achieving a superior piezoelectric property.…”
Section: Introductionmentioning
confidence: 99%
“…They observed polarization-electric field (P-E) hysteresis loops and two stable polarization states, which are inherent to ferroelectric materials, by piezoelectric force microscopy. 18) However, the ferroelectricity of the films might have been induced by the strain from the substrate, even if the clamping effect of the (111) orientation is smaller than that of the (100) orientation in the case of the epitaxially grown perovskite oxide films. 19) In this paper, we report on the film thickness dependences of the crystal structure and electrical properties of (111)-oriented epitaxial Bi(Mg 1=2 Ti 1=2 )O 3 films to investigate the contribution of substrate clamping to the ferroelectricity of these films, because the clamping effect becomes smaller with increasing film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…13) The piezoelectric (field-induced) strain by the application of a high voltage reaches a maximum of about 330 pm/V at x between 0.31 and 0.35. 13) Bi(Mg 1=2 Ti 1=2 )O 3 (BMT) also shows ferroelectricity with a large spontaneous polarization in film form [15][16][17] and cannot be obtained in bulk form unless high-pressure synthesis is carried out. 18,19) However, some of the authors revealed that a single-phase BT-BMT solid solution can be synthesized by a conventional method under ambient pressure if the BMT content is 50% or less, and BT-BMT samples with BMT contents up to 70% can be obtained with only a small amount of the bismuth oxide secondary phase.…”
Section: Introductionmentioning
confidence: 99%